Examining The Fundamental Role of School Gardening Programme and Its Impact on Malnutrition in South African Rural Communities - Malatji, Thabiso; Kgarose, Mathibedi; Setaise, Caroline; Makhubela, Daphney (Universitas Medan Area, 2023)
The notion of malnutrition remains the world’s most serious health problem and the single biggest contributor to child mortality. Although food gardens are not specifically mentioned, they have the potential to provide support for malnourished and sick people including children and adults and potentially provide nutritional diversity to support complementary feeding. This study aims to examine the role of the school gardening Programme and its impact on malnutrition in South African rural communities. Data reveals that many children in the rural communities of South Africa suffer from malnutrition and they are experiencing several health consequences. Moreover, this is common among the children at most primary and secondary schools. Therefore, the lack of economic resources, and absence of information regarding nutrition, and inadequate breastfeeding increase the chances and number of malnourished children in rural communities. This is a conceptual or abstract paper whereby the authors relied merely on secondary data and government documents in writing and achieving the set goals and objectives. The study concludes that school gardening programs have the potential to play a fundamental role in addressing malnutrition in South African rural communities. By providing learners with access to fresh produce, nutrition education, and promoting environmental sustainability, these programs can have a positive impact on the health and well-being of students and their communities.